The Interplay of Organizational Culture, Knowledge Management System, and Learning Evaluation in Improving English Language Skills: A Mixed-Method Study in Indonesian Pesantrens - Ma’arif, Samsul; Fathoni , AB. Musyafa; Suyudi, Suyudi; Yudi, Usman; Muna, Naily El (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study examines the interaction among organizational culture, knowledge management, and learning evaluation in improving English language competence in pesantrens in East Java, using a sequential exploratory mixed-methods design. Qualitative data were collected through interviews, observations, and focus group discussions with pesantren leaders, teachers, and students to identify context-specific dimensions of organizational culture, knowledge management practices, and evaluation systems, which subsequently informed the development of a quantitative instrument administered to 306 respondents across three pesantren. Quantitative analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) indicates that learning evaluation exerts the strongest positive influence on English language competence, underscoring the role of continuous assessment, feedback, and follow-up actions in shaping learning outcomes. Organizational culture also shows a positive contribution by fostering discipline, language habituation, and collective responsibility. In contrast, knowledge management demonstrates a negative relationship with English language competence, reflecting partial implementation, limited technological integration, and fragmented knowledge-sharing practices, as corroborated by qualitative findings. These results highlight the importance of aligning organizational culture, evaluation practices, and context-sensitive knowledge management to enhance English language learning in pesantren while maintaining their core educational values.